Driving Gen Z’s Buying Decisions: Testing Affiliate Marketing Effects Through the S–O–R Framework - Rihidima, Lidya Veronica Christy; Kusbianto, Nugraha (Journal of Business and Economics Research (JBE), 2025)
This research aims to examine the impact of affiliate marketing on the purchasing intentions of Generation Z in Indonesia using the Stimulus-Organism-Response (SOR) theoretical framework. This study also aims to fill the gap in previous literature by focusing on Generation Z as a group of digital native consumers and their online shopping behavior through affiliate marketing channels. This study uses an explanatory quantitative research design to examine the relationship between variables related to affiliate marketing and purchase intention among Generation Z. Data was collected through an online questionnaire distributed via social media such as Instagram and TikTok, targeting Generation Z in Indonesia who frequently make online purchases and are influenced by affiliate marketing. The sampling technique used was purposive sampling. The sample size in 190 respondents. The results of the study indicate that the information quality and virtual interactivity significantly influence Gen Z's trust (IQ -> TR = 0.199, VI-> TR = 0.238) and information quality significantly influence satisfaction (IQ->SA = 0.236), which in turn positively impact purchase intention. Virtual interactivity are the strongest factor in building trust (0.238), while satisfaction (0.396) is the most influential mediator in the relationship between affiliate marketing and purchase intention. The study also found that female respondents and Gen Z aged 20–22 (63 respondents, 33.2%) are more easily influenced by affiliate marketing in their online purchase intention.